2018
DOI: 10.1089/dna.2018.4312
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lncRNAs and Their Functional Network Associated with Chemoresistance in SW1990/GZ Pancreatic Cancer Cells by RNA Sequencing

Abstract: Drug resistance is a major problem in the treatment of pancreatic cancer (PC). Long noncoding (lnc)RNAs modulate a variety of cellular processes. This study was carried out to identify lncRNAs that are differentially expressed in drug-resistant PC by next-generation RNA sequencing. We identified 205 differentially expressed lncRNAs (DELs) and 847 differentially expressed mRNAs (DEMs) in a comparison of gemcitabine-resistant and -sensitive SW1990 human PC cells. The expression levels of 12 randomly selected lnc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 64 publications
1
24
0
Order By: Relevance
“…MIR210HG was validated in hypoxic HUVECs and human PTECs as hypoxia responding lncRNAs [16,17]. In addition, this lncRNA is a proposed potential tumor biomarker for glioma [22], colorectal adenocarcinoma [23], osteosarcoma [24], and pancreatic cancer [25]. In the present study, we reported that MIR210HG can be a potential biomarker of varicocele-related male infertility.…”
Section: Plos Onesupporting
confidence: 51%
“…MIR210HG was validated in hypoxic HUVECs and human PTECs as hypoxia responding lncRNAs [16,17]. In addition, this lncRNA is a proposed potential tumor biomarker for glioma [22], colorectal adenocarcinoma [23], osteosarcoma [24], and pancreatic cancer [25]. In the present study, we reported that MIR210HG can be a potential biomarker of varicocele-related male infertility.…”
Section: Plos Onesupporting
confidence: 51%
“…Consistent with these reports, we for the first time revealed that MIR210HG was transcriptionally activated by in HIF-1α under hypoxic conditions. Previously, MIR210HG has been demonstrated to be overexpressed in hepatocellular carcinoma ( 40 ), non-small cell lung cancer (NSCLC) ( 41 ), osteosarcoma ( 42 ), glioma ( 43 ) and chemoresistant pancreatic cancer ( 44 ). In invasive breast cancer patients, MIR210HG is highly expressed and confers a poor prognosis ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Voellenkle et al found that MIR210HG was induced by hypoxia in endothelial cells and mouse models of hindlimb ischemia, suggesting a regulatory function in hypoxia [23]. A coexpression network revealed a hub comprising lncRNAs (MIR210HG, SNHG1, and LOC729970) and mRNAs (RAB3D, DDX17, and SPNS2) that presumably mediate drug resistance in pancreatic cancer [24]. This information might illustrate its function in tumor biology [25].…”
Section: Discussionmentioning
confidence: 99%